Spread of Vector-borne Diseases and Neglect of Leishmaniasis, Europe - Jean-Claude Dujardin; Lenea Campino; Carmen Cañavate; Jean-Pierre Dedet; Luigi Gradoni; Ketty Soteriadou; Apostolos Mazeris; Yusuf Ozbel; Marleen Boelaert (Emerging Infectious Diseases, 2008)
The risk for reintroduction of some exotic vector-borne diseases in Europe has become a hot topic, while the reality of others is neglected at the public health policy level. Leishmaniasis is endemic in all southern countries of Europe, with ≈700 autochthonous human cases reported each year (3,950 if Turkey is included). Asymptomatic cases have been estimated at 30–100/1 symptomatic case, and leishmaniasis has up to 25% seroprevalence in domestic dogs. Even though leishmaniasis is essentially associated with Leishmania infantum and visceral leishmaniasis, new species, such as L. donovani and L. tropica, might colonize European sand fly vectors. Drug-resistant L. infantum strains might be exported outside Europe through dogs. Despite this possibility, no coordinated surveillance of the disease exists at the European level. In this review of leishmaniasis importance in Europe, we would like to bridge the gap between research and surveillance and control.